Ethno–medicobotany of Yavatmal District (M.S.) India - Chavan, V N; Bhogaonkar, P Y; Dhole, P A; Kshirsagar, P P (Plantae Scientia, 2020)
Yavatmal district is inhabited by about 14 tribal communities. First hand ethnomedicinal information was collected directly from field survey of tribal villages and forest areas of the district. Present paper deals with ethno medicinal uses of 78 plant species belonging to 47 families used locally for prevention and treatment of various diseases. Sixty two species are used in mono-herbal treatments, while 29 are used in poly-herbal formulations. Observations regarding exploitation of these species are also reported, which will help in conservation and restoration of the species.